2021
DOI: 10.3390/cancers13102438
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PGRMC1 Delays the Progression of Hepatocellular Carcinoma via Suppression of Pro-Inflammatory Immune Responses

Abstract: Pgrmc1 is a non-canonical progesterone receptor related to the lethality of various types of cancer. PGRMC1 has been reported to exist in co-precipitated protein complexes with epidermal growth factor receptor (EGFR), which is considered a useful therapeutic target in hepatocellular carcinoma (HCC). Here, we investigated whether Pgrmc1 is involved in HCC progression. In clinical datasets, PGRMC1 transcription level was positively correlated with EGFR levels; importantly, PGRMC1 level was inversely correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Although HCC progression was phenotypically suppressed in SHBG mice compared with that in WT mice, which is similar to our published data [28], EE2 could expose SHBG mice to HCC risk by triggering markedly pronounced hepatitis, fibrosis, and compensatory proliferation with AR activation. Although survival data are not included in the present study, it is expected that a substantially high number and burden of tumors might lead to a short survival period of HCC-bearing mice, similar to the previous study [29]. Our study highlights the clinical risk for men taking EE2, particularly those expressing high SHBG levels, and women ingesting EE2, particularly those with high androgen levels.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Although HCC progression was phenotypically suppressed in SHBG mice compared with that in WT mice, which is similar to our published data [28], EE2 could expose SHBG mice to HCC risk by triggering markedly pronounced hepatitis, fibrosis, and compensatory proliferation with AR activation. Although survival data are not included in the present study, it is expected that a substantially high number and burden of tumors might lead to a short survival period of HCC-bearing mice, similar to the previous study [29]. Our study highlights the clinical risk for men taking EE2, particularly those expressing high SHBG levels, and women ingesting EE2, particularly those with high androgen levels.…”
Section: Discussionsupporting
confidence: 66%
“…We analyzed whether HCC progression in SHBG EE2 mice is related to proliferation or inflammation-triggered proliferation. Results showed that SHBG EE2 substantially increased the growth factor response mediated by EGFR, which is known to be highly activated during hepatocarcinogenesis and is an inflammatory target for HCC therapy [29]. As a cell proliferation marker [43], PCNA levels were induced by SHBG EE2.…”
Section: Discussionmentioning
confidence: 97%
“…Lee et al [161] show that PGRMC1 is involved in a pro-inflammatory response involving EGFR in hepatocellular carcinoma. It will be interesting to see whether TSPO is involved in that system.…”
Section: Potential Early Eukaryotic Mapr Functions Deduced From Moder...mentioning
confidence: 99%
“…PGRMC1 activates the epidermal growth factor receptor (EGFR)-dependent PI3K/Akt pathway in breast cancer to promote inflammatory responses and tumor progression [378,386], and interacts with ESRα [148][149][150][151][152]371]. Lee et al [408] show that PGRMC1 is involved in an EGFRdependent inflammatory response in hepatocellular carcinoma, and Peluso and Pru [393] have reviewed the contribution of PGRMCs to ovarian and endometrial cancer.…”
Section: Pgrmc1 Affects Inflammationmentioning
confidence: 99%